1999
DOI: 10.1212/wnl.52.7.1403
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of apathy and depression in patients with dementia

Abstract: Apathy, but not depression, is associated with significantly more severe frontal lobe related cognitive deficits in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
130
5
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(156 citation statements)
references
References 20 publications
20
130
5
1
Order By: Relevance
“…These results suggested that, independently from clinical diagnosis, apathetic patients showed relevant executive impairments, in line with most previous studies [14,15,20,21,23,25,26]. In other terms, the present data indicated a strong association between apathy and alterations of cognitive functions mediated by prefrontal cortex, since apathetic and non-apathetic patients were matched for age, educational level and severity of general cognitive decline.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggested that, independently from clinical diagnosis, apathetic patients showed relevant executive impairments, in line with most previous studies [14,15,20,21,23,25,26]. In other terms, the present data indicated a strong association between apathy and alterations of cognitive functions mediated by prefrontal cortex, since apathetic and non-apathetic patients were matched for age, educational level and severity of general cognitive decline.…”
Section: Discussionsupporting
confidence: 92%
“…Apathy has also been observed in Alzheimer's disease (AD) since its early stages [24], and is associated with low functional autonomy, severe executive dysfunction and fast cognitive and functional decline [24][25][26][27]. Brain imaging studies in AD reported a significant association between apathy and abnormal perfusion in the frontal cortex and in the cingulate area [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors speculated that apathy might contribute directly to cognitive dysfunction in stroke patients. Our study showed that apathetic patients were more depressed; however, previous studies suggested that apathy and depression may be distinct but partially overlapping symptoms [6,9,14,36,37,38]. …”
Section: Discussioncontrasting
confidence: 80%
“…Since depression is also a common neuropsychiatric consequence of stroke, apathy and depression partially overlap in the clinical symptoms. However, apathy is an independent syndrome, distinct from depression [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although attentional shift was initially worse in the apathy group, this difference was no longer evident once the co-variates were accounted for. These findings are supported by studies of cognitive impairment in AD and MCI, which have also found significantly worse word list learning, verbal fluency, set shifting and naming in those with apathy compared to those without apathy (Kuzis et al, 1999;Sperry et al, 2001;Robert et al, 2006b;McPherson et al, 2002;Pluck and Brown, 2002;Starkstein et al, 1992).…”
Section: Impact Of Apathy On Cognitive Function In Pdmentioning
confidence: 70%